Does Nigella sativa supplementation improve cardiovascular disease risk factors? A comprehensive GRADE-assessed systematic review and dose-response meta-analysis of 82 randomized controlled trials - Ali Jafari; Helia Mardani; Amir Hossein Faghfouri; Zahra Mirzaei Fashtali; Mohtaram Hashemi; Matin Abdollahi Yousefabady; Reihane Javid; Sahar Golabi; Bahareh Arghavan; Vali Musazadeh; Mahshid Naghashpour (Pharmacological Research, 2025)
Aim: This systematic review and meta-analysis aimed to evaluate the effects of Nigella sativa (N. sativa) supplementation on metabolic and cardiovascular health outcomes. Methods: A comprehensive search of EMBASE, Scopus, PubMed, CENTRAL, and Web of Science databases was conducted up to August 2024. Study quality and certainty of evidence were assessed using the Cochrane Risk of Bias and Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) tools, respectively. Results: Eighty-two studies, including 79 quantitative and 3 qualitative studies published between 2008 and 2024, involving 5026 participants with interventions ranging from 1 to 48 weeks and doses varying from 200 to 4600 mg/day, were included. N. sativa supplementation significantly improved body fat percentage (BF%), body mass index (BMI), skeletal muscle mass (SMM), waist circumference (WC), weight, waist-to-hip ratio (WHR), diastolic blood pressure (DBP), systolic blood pressure (SBP), mean arterial pressure (MAP), fasting blood sugar (FBS), hemoglobin A1c (HbA1c), postprandial blood glucose (PPBG), quick insulin sensitivity check index (QUICKI), C-reactive protein (CRP), high-sensitivity CRP (hs-CRP), intercellular adhesion molecule-1 (ICAM-1), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), vascular cell adhesion molecule-1 (VCAM-1), atherogenic index (AI), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC) to HDL-C ratio, TC, triglycerides (TG), very-low-density lipoprotein cholesterol (VLDL-C), alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatinine, urea, catalase (CAT), malondialdehyde (MDA), superoxide dismutase activity (SOD) activity, and total antioxidant capacity (TAC). Conclusions: Our findings suggest that N. sativa could be a promising adjunct therapy for improving cardiovascular disease (CVD) risk factors.